QlikView Server and Publisher. - Redmond, Stephen (Packt Publishing, 2014)
This is a comprehensive guide with a step-by-step approach that enables you to host and manage servers using QlikView Server and QlikView Publisher. If you are a server administrator wanting to learn about how to deploy QlikView Server for server management, analysis and testing, and QlikView Publisher for publishing of business content then this is the perfect book for you. No prior experience with QlikView is expected.